THE RIGHTS OF CHILDREN REFUGEE IN TRANSIT COUNTRY UNDER THE CRC, A CASE OF INDONESIA: AN INTENDED NEGLIGENCE? - Debby Kristin; Chloryne Trie Isana Dewi (International Law Department, Faculty of Law Universitas Padjadjaran, 2021)
AbstractCivil wars in Middle Eastern countries and several countries in Africa have resulted in an increased influx of refugees seeking refuge in Indonesia every year. Although Indonesia is not their final destination, they prefer to wait in a transit country rather than experience terror and persecution in their home country., As a non-signatory country to the 1951 Geneva Convention, for humanitarian reasons, Indonesia allows those people who already in the territory of Indonesia to temporary stay until they status are clear. 28% of the refugees registered with the United Nations High Commissioner for Refugees (UNHCR) in Indonesia are under 18 years of age. Being a refugee child in a transit country keeps them away from the threat of war crimes in their country, nonetheless it turns out that there are basic rights that cannot be fully fulfilled. The 1989 Convention on the Rights of the Child (CRC) regulates state obligation to fulfil the rights of the child in any situation without discrimination. Indonesia as a transit country and state party to the CRC facing dilemma in assisting the child refugees. This article will analyse whether Indonesia has responsibility for child refugee in its jurisdiction as regulated in the CRC. By research, Indonesia can be considered fail to conduct its obligation under CRC. Hence Indonesia can be held responsible for its negligence in complying its obligation under the CRC. Nonetheless, there are measures that can be taken by the Indonesian Government through cooperation with international communities as well as corporations to tackle the challenges in implementing the CRC particularly in regards to refugee children. Keywords: Basic Rights, Refugee Children, State Responsibility AbstrakPerang sipil di negara Timur Tengah dan beberapa negara di Afrika menghasilkan gelombang pengungsi yang mencari perlindungan ke Indonesia meningkat setiap tahunnya. Mereka lebih memilih untuk menunggu di negara transit daripada harus merasakan teror dan persekusi di negara asalnya. Indonesia bukan negara peserta Konvensi Jenewa 1951, namun dengan alasan kemanusiaan menampung untuk sementara para pencari suaka sampai status mereka jelas berdasarkan penilaian UNHCR. Sebesar 28% dari pengungsi yang terdaftar di United Nations High Commissioner for Refugees (UNHCR) Indonesia berumur di bawah 18 tahun. Menjadi anak yang berada di negara transit memang menjauhkan mereka dari ancaman kejahatan perang di negaranya, namun ternyata tidak seluruh hak asasi mereka dapat dipenuhi di negara transit. Konvensi Hak Anak 1989 mengatur kewajiban negara untuk memenuhi hak asasi anak dalam situasi apapun tanpa diskriminasi. Indonesia sebagai negara transit dan juga a peratifikasi Konvensi Hak-hak Anak 1989 (KHA) menghadapi dilema dalam menghadapi anak-anak pencari suaka. Artikel ini akan menganalisa apakah Indonesia melakukan pelanggaran terhadap pemenuhan hak bagi para pengungsi anak sehingga dapat dikenai tanggung jawab negara. Indonesia dapat dikatakan gaal dalam memenuhi kewajibannya berdsarkan KHA sehingga dapat diminta pertanggungjawaban atas kelalalainya. Namun terdapat berbagai upaya yang dapat dilakukan oleh pemerintah Indonesia dengan bekerjasama dengan berbagai Lembaga internasional maupun nasional serta perusahaan untuk mengatasi permasalahan dalam penerapan KHA terutama terkait hak pengungsi anak. Kata Kunci: Hak-Hak Dasar, Pengungsi Anak, Tanggung Jawab Negara